Unilateral lower limb lymphedema resulting from a heart surgery performed 50 years prior - Onoda, Satoshi (Int J Surg Case Rep, 2015)
INTRODUCTION: Lymphedema is classified into two main types: secondary lymphedema accompanied by lymph node excision surgery or radiotherapy; and idiopathic lymphedema. Here we experienced a very rare case of lymphatic edema resulting from cardiac surgery that the patient underwent 50 years previously. PRESENTATION OF CASE: A 62-year-old woman experienced progressive unilateral lower leg lymphedema for recent years. After undergoing cardiac surgery at another hospital at the age of 12 years, she gradually developed left lower leg edema. The cause of the edema was unclear and it remained untreated. Her edema symptoms gradually worsened in recent years, so she consulted the plastic surgery division of our hospital. DISCUSSSION: Perhaps the lymphatic structures of affected individuals differ prior to disease onset. If the mechanism of lymphatic edema outbreak is elucidated, patients needing conservative and surgical therapy might be more easily identified. Knowing the outbreak mechanism of lymphatic edema would definitely ease the investigation of an unconventional case like this one. Conservative treatments for lymphedema, such as self-massage and compression therapy using garments, were immediately started. With these treatments, the leg volume and edema symptoms reduced. CONCLUSION: The research on the cause of this case may be important step for elucidating the source of secondary lymphatic edema.